2022
DOI: 10.1038/s41598-022-24498-7
|View full text |Cite
|
Sign up to set email alerts
|

Population admixtures in medaka inferred by multiple arbitrary amplicon sequencing

Abstract: Cost-effective genotyping can be achieved by sequencing PCR amplicons. Short 3–10 base primers can arbitrarily amplify thousands of loci using only a few primers. To improve the sequencing efficiency of the multiple arbitrary amplicon sequencing (MAAS) approach, we designed new primers and examined their efficiency in sequencing and genotyping. To demonstrate the effectiveness of our method, we applied it to examining the population structure of the small freshwater fish, medaka (Oryzias latipes). We obtained … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 58 publications
0
2
0
Order By: Relevance
“…Our study has demonstrated that ISSRseq can infer the parentage (lineage) relationships of fish fry even without broodstock information, showcasing its potential for marker‐assisted selection. Furthermore, although ISSRseq markers, like RADseq, do not require prior genomic information, they can still be mapped to a reference genome when available (Fujimoto et al, 2022; Lee et al, 2019). This allows further exploration of whether they originate from genic regions and are related to specific gene functions.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our study has demonstrated that ISSRseq can infer the parentage (lineage) relationships of fish fry even without broodstock information, showcasing its potential for marker‐assisted selection. Furthermore, although ISSRseq markers, like RADseq, do not require prior genomic information, they can still be mapped to a reference genome when available (Fujimoto et al, 2022; Lee et al, 2019). This allows further exploration of whether they originate from genic regions and are related to specific gene functions.…”
Section: Discussionmentioning
confidence: 99%
“…This allows further exploration of whether they originate from genic regions and are related to specific gene functions. This potential may be further exploited in the future (Fujimoto et al, 2022; Lee et al, 2019).…”
Section: Discussionmentioning
confidence: 99%